Lake Morphometry and River Network Controls on Evasion of Terrestrially Sourced Headwater CO2. Issue 1 (7th January 2021) - Brinkerhoff, C. B.; Raymond, P. A.; Maavara, T.; Ishitsuka, Y.; Aho, K.S.; Gleason, C. J.
Abstract: Lakes are central components of the inland water system distinct from, yet inextricably connected to, river networks. Currently, existing network‐scale biogeochemistry research, although robust, typically treats each of these components separately or reductively. Here, we incorporate lake morphometry into a fully connected stream/lake network for the Connecticut River watershed and model potential evasion of terrestrially sourced headwater CO2 as transported through the network, ignoring in‐stream production. We found that approximately 25%–30% of total potential soil CO2 evasion occurs in lakes, and percent evasion is inversely related to streamflow. A lake's ability to evade CO2 is controlled by residence time and size: most lakes with residence time over 7 days or surface area greater than 0.004 km 2 evade functionally all terrestrial CO2 entering from upstream, precluding further downstream transport. We conclude that lakes are important for soil CO2 degassing and that this coupled river/lake approach is promising for CO2 studies henceforth. Plain Language Summary: River networks are both delivery systems and active transformers of constituents (sediment, nutrients, biota, heat) as they carry them to the sea. An important and overlooked component of these networks are lakes: lakes dominate total water storage of surface water in river networks and have vastly different hydraulics than rivers. Despite this knowledge, most greenhouse gas (GHG) research addresses lakes and rivers separately or reductively. To address this, we built a fully connected model for over 98, 000 rivers and lakes in the Connecticut River watershed and found that lakes emit substantially more carbon dioxide than rivers per unit (potentially 25%–30% of the total emission from the system), and that almost all lakes emit almost all the carbon dioxide that enters their waters. These findings demonstrate the importance of connected lakes to drainage network GHG exchange and corroborate the need to better integrate lakes into our understandings of GHG emissions from freshwater systems in a formalized framework. Key Points: We model potential evasion of terrestrially sourced headwater CO2 from over 98, 000 river and lake units in the Connecticut River watershed Lakes are responsible for approximately 25%–30% of potential CO2 evasion, as influenced by streamflow and stream order Lake CO2 evasion efficiency is a function of residence time and size, where larger lakes evade functionally 100% of CO2 from upstream